Keanekaragaman Zooplankton di Perairan Kepulauan Togean Kabupaten Tojo Una-Una, Sulawesi Tengah - Miswan Miswan (Biology Department, Mathematics and natural science, Tadulako University, 2010)
The structure of plankton community have been conducted in Togean Island from September 2008 untill Februari 2009, it used descriptive method. The result of the structure of zooplankton community indicate plankton range from 0,862-0.879, with value of biodiversity range from 0.328-0.330, for the value of variety of fitoplankton range from 0.328-0.329 and found marozoobenthos range from 26-27 individual/L, with variety value of benthos range from 0.831-0.835 with value of biodiversity range from 0.339-0.341. This indicator is not indicate the ecology pressure, but is not depend on river condition. Key words: Biodeversity, zooplankton, and Togean.